Effect of "Gol-e-ghand", a mixture of rose petals and honey, on migraine attacks: a before-after pilot study - A. Maddahian; M. Togha; S. Sahranavard; S.M. Riahi; S. Dehghan; M. Movahhed (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Migraine is the seventh most common cause of disability among all ailments according to the World Health Organization. Despite the availability of some medicines for prevention of migraine, their complications are a cause for concern. Traditional system of medicine and use of medicinal herbs can be beneficial in management of migraine. "Gol-e-ghand" is one of the most commonly prescribed products for the management of headaches in the Iranian traditional medicine. The present study was designed to evaluate the effect of "Ghol-e-ghand" on decreasing the frequency of migraine attacks. Methods: Nineteen migraine patients, who met the eligibility criteria, according to the International Headache Society diagnostic criteria were assigned to the intervention. The study was conducted as a before-after clinical trial and included two phases of drug administration. Propranolol was given during the first phase, while "Ghol-e-ghand" was administered along with propranolol in the second phase. The severity, duration, and frequency of headaches were measured before and after the intervention. Results: The analysis showed that "Ghol-e-ghand" decreased the frequency of migraine (20%, p=0.04), but it was not effective in decreasing the duration and severity of the attacks. Conclusion: "Ghol-e-ghand"can be suggested in migraine patients for reducing frequency of attacks.